Buddhist goals of journalism and the news paradigm - Gunaratne, Shelton A. (Javnost (Ljubljana), 2009)
This essay compares and contrasts the goals of Buddhist journalism with the general traits of the dominant/ Western news paradigm to demonstrate the gap between the moral aspirations of the Orient and the instrumental materialistic traits revealed through the performance of the dominant/Western paradigm, which has even marginalised the moral imperatives of the Decalogue The essay goes on to assess the unique opportunities offered by Buddhist journalism, which no other genre of journalism - developmental, civic/public, peace - is able to off er to improve the quality of journalism, journalists and their profession.
Keywords: journalism; novinarstvo; informiranje; javno obveščanje; poklicna etika; Buddhism; budizem